ChemInform Abstract: Advances in the Development of Pyridinone Derivatives as Non‐Nucleoside Reverse Transcriptase Inhibitors. Issue 11 (February 2016) - Vite‐Caritino, Hugo; Mendez‐Lucio, Oscar; Reyes, Hector; Cabrera, Alberto; Chavez, Daniel; Medina‐Franco, Jose L.
Abstract: Review: 43 refs.